2017
DOI: 10.14735/amko20173s22
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in the Treatment of Lung Cancer

Abstract: 1 Onkologická a radioterapeutická klinika LF UK a FN Plzeň 2 Biomedicínské centrum LF UK v Plzni 3 Klinika pneumologie a ftizeologie LF UK a FN Plzeň Souhrn Východiska: Karcinom plic zaujímá přední místa v incidenci i mortalitě nádorových onemocnění celosvětově, i v České republice. Přes významné pokroky v systémové onkologické léčbě dosažené v poslední době patří plicní karcinom mezi zhoubné nádory s nejhorší prognózou a potřeba hledání inovativních terapeutických prostředků a metod je zde stále velmi vysoká.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Most lung‐originated cancers, referred to as primary lung cancer, occur in epithelial cells, which are thin and lie on the alveolar surfaces of the lung for gas exchange 3. Clinically, lung cancer is mainly divided into small‐cell lung cancer and non–small cell lung cancer 4,5. Despite the fact that significant progresses have been made in systemic oncology treatments, lung cancer prognosis is far from satisfactory, which drives the need for innovative therapies and methods to treat this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Most lung‐originated cancers, referred to as primary lung cancer, occur in epithelial cells, which are thin and lie on the alveolar surfaces of the lung for gas exchange 3. Clinically, lung cancer is mainly divided into small‐cell lung cancer and non–small cell lung cancer 4,5. Despite the fact that significant progresses have been made in systemic oncology treatments, lung cancer prognosis is far from satisfactory, which drives the need for innovative therapies and methods to treat this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although therapeutic advances, including surgical resection and chemoradiotherapy, have improved the prognosis of patients with lung cancer, the overall survival rates and quality of life remain unsatisfactory. The migration and invasion of cancer cells that results in metastasis presents the greatest challenge to clinical therapy (3). Hence, investigation of the molecular mechanisms of lung cancer cell invasion and migration may provide novel evidence to improve clinical therapy.…”
Section: Introductionmentioning
confidence: 99%
“…m 6 A score is a reliable tool that can be used to assess m 6 A-TME. TMB alone is not a good predictor for the effect of immune checkpoint inhibitors, and the combined m 6 A score can improve the ability of TMB to predict immunotherapy [ 25 27 ]. Further studies revealed that higher PD-L1 expression in low m 6 A received better immunotherapy, suggesting that the lymphoid infiltrating cells in the tumor microenvironment can enhance the efficacy of immune check blocking therapy, while stromal cells can exert an anti-immune check blocker effect.…”
Section: Discussionmentioning
confidence: 99%